Legal and Socioeconomic Issues in the Implementation of Muzara’ah Contracts: A Sharia Economic Law Perspective - Masruha; Moh Khozin (Jurnal Dinamika Ekonomi Syariah, 2025)
This study discusses the problems in the implementation of the muzara'ah contract, which is a form of agricultural cooperation between land owners (shahibul ardh) and cultivators (amil) based on the principle of profit sharing, which is still widely practiced in rural areas, especially in Rujing Hamlet, Sungai Teluk Village, Sangkapura District. The problems that arise in practice in the field indicate deviations from sharia provisions, including: unclear wording of the contract, profit sharing that is not agreed upon transparently, and poor public understanding of the rights and obligations of each party. In addition, the absence of supervision from religious institutions or village officials exacerbates the inequality in this cooperative relationship. The research method used is a descriptive qualitative approach with data collection techniques through direct observation, in-depth interviews with the parties involved (land owners, cultivators, community leaders), and supporting documentation. Data analysis was carried out by referring to classical and contemporary muamalah fiqh theories. Based on the research results, it can be concluded that the problems of muzara'ah contracts at the study location are related to three main aspects: (1) legal aspects, namely the absence of written recording of contracts and ignoring the principles of clarity and agreement; (2) economic aspects, in the form of inequality in the distribution of results and low profits obtained by cultivators; and (3) socio-religious aspects, in the form of minimal literacy in muamalah fiqh among the actors.